Mechanically responsive luminescent films based on copper iodide clusters. Issue 25 (11th June 2021) - Utrera-Melero, Raquel; Huitorel, Brendan; Cordier, Marie; Massuyeau, Florian; Mevellec, Jean-Yves; Stephant, Nicolas; Deniard, Philippe; Latouche, Camille; Martineau-Corcos, Charlotte; Perruchas, Sandrine
Abstract : A mechanochromic luminescent copper iodide cluster is reported whose luminescence is exalted in response to mechanical stress. The underlying mechanism has been investigated along with the preparation of mechanically responsive films. Abstract : Mechanochromic luminescent materials exhibiting emission changes easily detectable by simple means present appealing applicative perspectives for strain detection. Along with design investigations, an in-depth understanding of the mechanochromism mechanism is of utmost importance for guiding the development of such stimuli-responsive devices. In this article, an original luminescent mechanochromic copper iodide cluster and its utilization as an active component for the synthesis of mechanically responsive films are reported. This formulated compound [Cu4 I4 (PPh2 i-Pr)4 ] displays a contrasted emission off–on effect upon mechanical solicitations. Structural characterization and spectroscopic analyses supported by theoretical investigations permit to attribute the mechanochromic mechanism to the structural changes of the molecular cluster at the defects created locally in the crystalline structure. The non-classical luminescence behaviour of the pristine crystalline cluster was rationalized by density functional theory calculations demonstrating that the very long Cu–Cu distance destabilizes the emissive triplet state of the classical cluster core. The shortening of these intramolecular Cu–Cu contacts upon mechanical forces permits the recovery of the classical luminescence properties of cubane copper iodide clusters with an intense room temperature emission. Mechanically responsive films based on the studied cluster were prepared by a direct synthesis method within the substrate. These films exhibit high contrasted luminescence mechanochromic properties with writing and erasing activating and deactivating, respectively, the emission of the photoactive component. The mechanochromic phenomenon was distinctly followed by scanning electron microscopy.